Vam analysis of local e-commerce acceptance - Ferry Bakti; Ari Amir; Burham Isnanto; Agus Dendi (Institute of Accounting Research and Novation (IARN), 2024)
This study evaluated the acceptance of HP Market Online Babel, a local e-commerce platform in Pangkalpinang, using a modified Value-based Adoption Model. The research focused on analyzing the influence of content marketing and influencer marketing on purchase intention, considering the mediating role of customer engagement. The study's objectives included analyzing the direct effects of content marketing and influencer marketing on customer engagement and purchase intention, and evaluating the mediating role of customer engagement in the relationship between digital marketing strategies and purchase intention. The research employed a quantitative approach with a cross-sectional survey design. The sample consisted of 100 active users of HP Market Online Babel, selected through purposive sampling. Data collection was conducted using an online questionnaire, and data analysis involved simple regression techniques and path analysis using SPSS software. The results revealed significant positive influences of content marketing and influencer marketing on customer engagement and purchase intention. Customer engagement played a mediating role in the relationship between both digital marketing strategies and purchase intention. Content marketing, particularly the informative content aspect, had the strongest impact in the research model. The study contributed to the development of the Value-based Adoption Model by integrating digital marketing strategies in the context of local e-commerce. The findings affirmed the importance of quality content and the strategic role of influencers in increasing customer engagement and driving purchase intention on local digital platforms. The results provided practical guidance for managers in optimizing digital marketing strategies, potentially improving business performance in the competitive local e-commerce market.